SOSIALISASI SUBAK SEBAGAI WARISAN BUDAYA DUNIA KEPADA SISWA SMU DI KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR - WINDIA, WAYAN; WIDYANTARA, I WAYAN; DJELANTIK, A.A.A WULANDIRA SAWITRI; WIJAYANTI, PUTU UDAYANI; DEWI, IDA AYU LISTIA; HANDAYANI, M.TH. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.5, Desember 2015, 2016)
Abstract Noble values ??contained in Subak finally set to make UNESCO as World Cultural Heritage in need of protection. The challenge is not only coming from the onslaught of tourism alone but the biggest challenge comes from farmers themselves , namely the lack of interest of young generation to carry on the profession as a farmer . This led to concerns about the sustainability and preservation of the water control system . Subak as one of the world 's cultural heritage contained in Sub Sukawati Gianyar regency which Subak Kulub Atas , Subak Kulub Bawah , and Subak Pulagan . Very important for the socialization of Subak as a world heritage , especially on the definition and management to the surrounding communities and the general location of the high school students in the District Sukawati Gianyar regency . Service activities that have been conducted in SMU 1 Sukawati, these students showed enthusiasm in listening to the material that we provide . After counseling , community service our team provides time for students to discuss around the water control system and world heritage , and there are many students who are interested and ask questions about how to preserve Subak and what they should do as the younger generation . As their young people are less interested in working in the agricultural sector , but they have the desire to preserve subak . Keywords: subak, world cultural heritage, agricultural